1997
DOI: 10.1080/00102209708935719
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Vent Area Location on Hydrogen-Air Mixture Deflagration in Large-Scale Vessel

Abstract: The results of large-scale experiments on combustion of local hydrogen-air mixtures in a chamber of 20 nr' volume are presented. It has been shown that, for mixtures with a relatively high laminar burning velocity, containing 30 % (vol.) hydrogen in air, the explosion pressure and the explosion pressure rise rate decrease more rapidly in the case where the vent area is located in the vicinity of a local combustion mixture. For mixtures with a relatively low laminar burning velocity, containing 10% (vol.) hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It is found that the space structure and shape have great influence on the law of explosion especially in the overpressure time history and flame propagation. The differences between the space structure and the shape contain the L/D ratio [2], vent size or location [3][4][5], obstacle shape or number [6][7][8], and turnings or bends [9,10]. Especially for the turnings or bends, researchers have made some findings and discoveries.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the space structure and shape have great influence on the law of explosion especially in the overpressure time history and flame propagation. The differences between the space structure and the shape contain the L/D ratio [2], vent size or location [3][4][5], obstacle shape or number [6][7][8], and turnings or bends [9,10]. Especially for the turnings or bends, researchers have made some findings and discoveries.…”
Section: Introductionmentioning
confidence: 99%